Adhesive composition, positive electrode plate, secondary battery and power consuming device
A fluorine-containing polymer blend with specific molecular weights addresses the adhesion challenges of conventional adhesives, improving battery cycle performance and energy density by ensuring strong adhesion and flexibility at low additive amounts.
Patent Information
- Application Number
- JP2024535262
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-08-30
- Filing Date
- 2023-04-14
- Publication Date
- 2024-12-26
- Estimated Expiration
- 2043-04-14
Smart Images

Figure 2024546830000001_ABST
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application references PCT patent application No. PCT / CN2022 / 099187, filed on June 16, 2022, entitled "ADHESIVE AND ITS MANUFACTURING METHOD AND APPLICATION," CN patent application No. 202211044631.4, filed on August 30, 2022, entitled "FLUORINE-CONTAINING POLYMER, ITS MANUFACTURING METHOD AND USE, POSITIVE ELECTRODE SLURRY, SECONDARY BATTERY, BATTERY MODULE, BATTERY PACK, AND POWER CONSUMPTION DEVICE," CN patent application No. 202211052014.9, filed on August 30, 2022, entitled "FLUORINE-CONTAINING POLYMER, ITS MANUFACTURING METHOD AND USE, POSITIVE ELECTRODE SLURRY, SECONDARY BATTERY, BATTERY MODULE, BATTERY PACK, AND POWER CONSUMPTION DEVICE," and CN patent application No. 202211046282.X, filed on August 30, 2022, entitled "ADHESIVE, MANUFACTURING METHOD, POSITIVE ELECTRODE PLATE, SECONDARY BATTERY, AND POWER CONSUMPTION DEVICE," all of which are incorporated by reference into this application.
[0002] The present application relates to the field of secondary battery technology, and in particular to an adhesive, a manufacturing method, a positive electrode plate, a secondary battery, a battery module, a battery pack, and a power consuming device. [Background technology]
[0003] In recent years, secondary batteries have been widely applied in energy storage power systems such as hydroelectric, thermal, wind and solar power plants, as well as in multiple fields such as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace, etc. As the application of secondary batteries becomes more widespread, higher requirements are being placed on their cycle performance, service life, etc.
[0004] Adhesives are commonly used materials in secondary batteries, and are in high demand for battery plates, separators, packaging, etc. However, conventional adhesives have poor adhesion and often require large amounts of additives to meet the adhesive strength requirements of the plates, which limits the improvement of the energy density of batteries. Therefore, conventional adhesives still need to be improved. Summary of the Invention
[0005] The present application has been made in view of the above problems, and has an object to provide an adhesive that can exhibit excellent adhesive strength even at a low addition amount and has good processability.
[0006] In order to achieve the above object, a first aspect of the present application provides an adhesive, the adhesive comprising a first fluorine-containing polymer and a second fluorine-containing polymer, the weight average molecular weight of the first fluorine-containing polymer being 1.5 million to 5 million, and the weight average molecular weight of the second fluorine-containing polymer not exceeding 600,000.
[0007] This adhesive can ensure that the plates have sufficient adhesion at low loadings, improving the cycling performance of the battery.
[0008] In any embodiment, the mass content of the second fluorine-containing polymer is 0.1% to 10% based on the total mass of the adhesive composition.
[0009] By controlling the mass ratio of the first fluorine-containing polymer to the second fluorine-containing polymer within an appropriate range, the adhesive can have excellent adhesive strength to the electrode plate even at a low addition amount, and can improve the capacity retention rate during the cycle process of the battery. By adding a small amount of the second fluorine-containing polymer to the first fluorine-containing polymer, the crystallinity and processability of the adhesive can be effectively improved, and the manufacturing cost can be reduced, while the cycle performance of the battery can be further improved.
[0010] In either embodiment, the adhesive composition has a crystallinity of less than 45%, optionally 15%-45%.
[0011] By adding the second fluorine-containing polymer to the first fluorine-containing polymer, the crystallinity of the adhesive can be effectively reduced and the flexibility of the electrode plate can be improved.
[0012] In either embodiment, the first fluorine-containing polymer comprises structural units derived from vinylidene fluoride.
[0013] In any embodiment, the first fluorine-containing polymer further comprises a structural unit according to formula I: [ka] Here, R1 includes one or more of hydrogen, fluorine, chlorine, and trifluoromethyl groups.
[0014] In any embodiment, the polydispersity coefficient of the first fluorine-containing polymer is from 1.5 to 2.5, and optionally from 2 to 2.3.
[0015] By setting the polydispersity coefficient of the first fluorine-containing polymer within a suitable range, the electrode plate has excellent adhesion and the capacity retention rate during the cycle process of the battery can be improved, and the suitable polydispersity coefficient of the first fluorine-containing polymer can effectively increase the solid content of the slurry and reduce the production cost.
[0016] In any embodiment, the crystallinity of the first fluorine-containing polymer is from 34% to 48%, optionally 40%-48%.
[0017] In any one of the embodiments, a glue solution containing the first fluorine-containing polymer at a mass content of 4% produced by dissolving the first fluorine-containing polymer in N-methylpyrrolidone has a viscosity of 2400 mPa·s to 5000 mPa·s, and optionally 3500 to 5000 mPa·s.
[0018] When preparing a positive electrode slurry, the adhesive must have a certain viscosity to prevent the precipitation of the positive electrode active material and auxiliary agents such as the conductive agent, and to allow the slurry to be placed relatively stably. In the prior art, in order to achieve a viscosity of the glue solution of 2400 mPa·s to 5000 mPa·s, it is necessary to contain an adhesive whose mass content is at least 7% based on the mass of the glue solution, but the first fluorine-containing polymer of the present application can achieve the expected viscosity of the glue solution with a usage amount of 4%, providing a basis for reducing the content of the adhesive in the positive electrode membrane layer.
[0019] In any embodiment, the first fluorine-containing polymer includes one or more of polyvinylidene fluoride, vinylidene fluoride-trifluorochloroethylene copolymer, vinylidene fluoride-hexafluoropropylene copolymer, vinylidene fluoride-trifluorochloroethylene-hexafluoropropylene copolymer, vinylidene fluoride-tetrafluoroethylene-hexafluoropropylene copolymer, and vinylidene fluoride-trifluorochloroethylene-tetrafluoroethylene-hexafluoropropylene copolymer.
[0020] In any embodiment, the second fluorine-containing polymer comprises a structural unit shown in formula II: [ka] where R2 and R3 are each independently hydrogen, halogen, or C containing at least one fluorine atom. 1-3 Contains at least one alkyl group.
[0021] In any embodiment, R2 and R3 each independently comprise at least one of hydrogen, fluorine, chlorine, and a trifluoromethyl group.
[0022] In either embodiment, the end groups of the second fluorine-containing polymer contain hydroxyl or ester groups.
[0023] The second fluorine-containing polymer has a small weight average molecular weight and a high mass content of end group, so the end group has a relatively large effect on the performance of the second fluorine-containing polymer.The end group of the second fluorine-containing polymer contains a hydroxyl group or an ester group, which can effectively improve the adhesion of the second fluorine-containing polymer and reduce the decrease in the plate adhesion performance caused by adding the second fluorine-containing polymer.
[0024] In any embodiment, the second fluorine-containing polymer has a weight average molecular weight of 5,000 to 600,000.
[0025] In any embodiment, the second fluorine-containing polymer includes one or more of polytetrafluoroethylene, polyvinylidene fluoride, poly(vinylidene fluoride-hexafluoropropylene) copolymer, poly(vinylidene fluoride-tetrafluoroethylene) copolymer, poly(vinylidene fluoride-fluorochloroethylene) copolymer, and poly(vinylidene fluoride-tetrafluoroethylene-hexafluoropropylene) copolymer.
[0026] A second aspect of the present application provides a method for producing an adhesive composition, comprising: producing a first fluorine-containing polymer: carrying out a first polymerization reaction on a raw material containing a vinylidene fluoride monomer under polymerizable conditions to produce a first fluorine-containing polymer, the weight average molecular weight of the first fluorine-containing polymer being 1.5 million to 5 million; producing a second fluorine-containing polymer: carrying out a second polymerization reaction on a fluorine-containing monomer under polymerizable conditions to produce a second fluorine-containing polymer, the weight average molecular weight of the second fluorine-containing polymer not exceeding 600,000; and blending: blending the first fluorine-containing polymer and the second fluorine-containing polymer to produce an adhesive composition.
[0027] In any embodiment, the first method for producing a fluorine-containing polymer specifically includes: carrying out a first polymerization reaction for 6 to 12 hours in a non-reactive gas atmosphere at a reaction pressure of 6 MPa to 8 MPa and a reaction temperature of 45°C to 60°C for a raw material including vinylidene fluoride monomer; adding a chain transfer agent and lowering the pressure in the reaction system to 2 MPa to 2.5 MPa to terminate the reaction, and then performing solid-liquid separation to leave a solid phase and obtain a first fluorine-containing polymer.
[0028] In any embodiment, the second method for producing a fluorine-containing polymer specifically includes: A second polymerization reaction is carried out for 0.5 to 8 hours with at least one monomer represented by formula III in a non-reactive gas atmosphere, at 0.1-5 MPa, and at a reaction temperature of 60°C to 90°C, and the reaction is terminated and separated into a solid and liquid to obtain a second fluorine-containing polymer while leaving a solid phase; [ka] Here, R4 and R5 are each independently hydrogen, halogen, or C containing at least one fluorine atom. 1-3 Contains at least one alkyl group.
[0029] In any embodiment, the second polymerization reaction comprises: adding a solvent and a dispersant to a vessel and filling said vessel with a non-reactive gas; The method further includes the steps of adding a monomer represented by formula III, raising the temperature to 60° C. to 90° C., and adding a second initiator and a chain transfer agent to carry out a second polymerization reaction.
[0030] In either embodiment, the second initiator comprises an inorganic peroxide and may be selected from potassium persulfate or ammonium persulfate.
[0031] According to the results of the nuclear magnetic test, when inorganic peroxide is used as the initiator, the end group of the second fluorine-containing polymer includes -CF2-CH2OH or -CF2-CH2OOCCH3. The presence of the hydroxyl group and the ester group in the end group can effectively improve the adhesion of the second fluorine-containing polymer, and reduce the deterioration of the adhesive performance of the adhesive composition caused by its addition.
[0032] In one embodiment, the weight content of the initiator is 3%-12% based on the total weight of the monomers of formula III.
[0033] In either embodiment, the chain transfer agent comprises one or more of cyclohexane, isopropyl alcohol, methanol, and acetone.
[0034] A third aspect of the present application provides a positive electrode plate, the positive electrode plate including a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, the positive electrode film layer including a positive electrode active material, a conductive agent, and an adhesive according to any of the embodiments or an adhesive produced by the production method according to any of the embodiments.
[0035] This positive electrode plate has excellent adhesive strength even with a low amount of adhesive added.
[0036] In any embodiment, the mass fraction of the adhesive does not exceed 1.2%, based on the total mass of the positive electrode membrane layer.
[0037] By controlling the mass fraction of the adhesive within an appropriate range, it is possible to ensure that the plate has sufficient adhesive strength while improving the loading amount of the active material in the battery plate, thereby contributing to further improving the power performance of the battery.
[0038] In either embodiment, the positive electrode active material is a lithium-containing transition metal oxide.
[0039] In any embodiment, the lithium-containing transition metal oxide is at least one of lithium iron phosphate or lithium nickel cobalt manganese oxide, or doped modifications thereof, or conductive carbon-coated, conductive metal-coated, or conductive polymer-coated modifications thereof.
[0040] A fourth aspect of the present application provides a secondary battery, the secondary battery including an electrode assembly and an electrolyte, the electrode assembly including a separator, a negative electrode plate, and the positive electrode plate of the third aspect of the present application.
[0041] A fifth aspect of the present application provides a power consuming device, the power consuming device including the secondary battery of the fourth aspect of the present application. [Brief description of the drawings]
[0042] [Figure 1] 1 is a schematic diagram of a secondary battery according to an embodiment of the present application; [Diagram 2] FIG. 2 is an exploded view of the secondary battery according to the embodiment of the present application shown in FIG. [Diagram 3] 1 is a schematic diagram of a battery module according to an embodiment of the present application; [Figure 4] 1 is a schematic diagram of a battery pack according to an embodiment of the present application; [Diagram 5] FIG. 5 is an exploded view of the battery pack according to the embodiment of the present application shown in FIG. 4. [Figure 6] 1 is a schematic diagram of a power consuming device in which a secondary battery according to an embodiment of the present application is used as a power source; DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0043] Hereinafter, with reference to the drawings, embodiments specifically disclosing the adhesive composition and its manufacturing method, the positive electrode plate, the secondary battery, the battery module, the battery pack, and the electric device of the present application will be described in detail. However, unnecessary detailed description may be omitted. For example, detailed description of well-known matters and duplicated description of the same structure may be omitted. This is to avoid the following description from becoming unnecessarily long and to allow those skilled in the art to easily understand. Note that the drawings and the following description are provided to allow those skilled in the art to fully understand the present application, and are not intended to limit the subject matter described in the claims.
[0044] The "ranges" disclosed in this application are defined in the form of lower and upper limits, and a given range is defined by selecting one lower limit and one upper limit, and the selected lower and upper limits define the boundaries of the particular range. Such defined ranges may be inclusive or exclusive of the extreme values, and may be arbitrarily combined, i.e., any lower limit may be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a particular parameter, it is understood that ranges of 60-110 and 80-120 are also envisaged. However, if 1 and 2 are listed as minimum range values, and 3, 4, and 5 are listed as maximum range values, the ranges 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5 are all envisaged. In this application, unless otherwise specified, the numerical range "ab" represents a shorthand representation of any combination of real numbers from a to b, where a and b are both real numbers. For example, the numerical range "0-5" represents a list of all real numbers between "0-5" already listed in this specification, and "0-5" is just a shorthand representation of combinations of these numbers. Also, expressing a parameter as an integer ≧2 is equivalent to disclosing that the parameter is, for example, the integers 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0045] Unless otherwise stated, all the embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0046] Unless otherwise stated, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0047] Unless otherwise stated, all steps in this application may be performed in sequence or randomly, and preferably in sequence. For example, the method includes steps (a) and (b) to mean that the method may include steps (a) and (b) performed in sequence, or may include steps (b) and (a) performed in sequence. For example, the method mentioned above may further include step (c) to mean that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), may include steps (a), (c) and (b), may include steps (c), (a) and (b), etc.
[0048] Unless otherwise specified, the terms "comprise" and "comprises" referred to in this application may be open ended or closed ended. For example, the terms "comprise" and "comprises" may further include or include other ingredients not listed, or may include or include only the ingredients listed.
[0049] Unless otherwise stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, "A or B" is satisfied if A is true (or exists) and B is false (or does not exist), if A is false (or does not exist) but B is true (or exists), or if both A and B are true (or exist).
[0050] Fluorine-containing polymers are one of the most widely used adhesives in secondary batteries at present. However, the viscosity of conventional fluorine-containing polymers is low, and they often need to be added in large amounts to ensure effective adhesion of active materials, thereby achieving effective adhesion of electrodes. However, the increase in the amount of conventional fluorine-containing polymers reduces the loading amount of active materials in electrodes, which affects the improvement of the power performance of the battery, making it difficult to meet the requirements for the cycle performance of the battery.
[0051] [glue] The present application provides an adhesive composition, comprising a first fluorine-containing polymer and a second fluorine-containing polymer, wherein the first fluorine-containing polymer has a weight average molecular weight of 1.5 million to 5 million, and the second fluorine-containing polymer has a weight average molecular weight not exceeding 600,000.
[0052] As used herein, the term "adhesive composition" is a mixture that forms a colloidal solution or dispersion in a dispersing medium.
[0053] In this specification, the term "fluorine-containing polymer" refers to a polymer whose main synthetic monomer is a fluorine-containing monomer, and the polymer includes, on the one hand, a chemically uniform aggregate of macromolecules produced by polymerization reaction, but with different degrees of polymerization, molar masses and chain lengths. On the other hand, the term also includes derivatives of such macromolecular aggregates formed by polymerization reaction, i.e. compounds obtained by reaction, for example addition or substitution, of functional groups in the macromolecules, and which may be chemically uniform or chemically heterogeneous. In this specification, the fluorine-containing polymer includes homopolymers and also copolymers.
[0054] As used herein, the term "weight average molecular weight" is the sum of the products of the weight fractions of molecules of different molecular weights in a polymer and their corresponding molecular weights.
[0055] In some embodiments, the dispersion medium of the adhesive composition is an oil-based solvent, examples of which include, but are not limited to, dimethylacetamide, N,N-dimethylformamide, N-methylpyrrolidone, acetone, dimethylcarbonate, ethylcellulose, and polycarbonate, i.e., the adhesive is dissolved in the oil-based solvent.
[0056] In some embodiments, the adhesive composition is used to hold the electrode active material and / or conductive agent in place and adhere them to the conductive metal members to form the electrode.
[0057] In some embodiments, the adhesive composition is used as a positive electrode adhesive to adhere a positive electrode active material and / or a conductive agent to form an electrode.
[0058] In some embodiments, the adhesive composition is used as a negative electrode adhesive to adhere a negative electrode active material and / or a conductive agent to form an electrode.
[0059] In some embodiments, the weight average molecular weight of the first fluorine-containing polymer is 1.5 million to 5 million. In some embodiments, the weight average molecular weight of the first fluorine-containing polymer is 1.5 million, 2 million, 2.5 million, 3 million, 3.2 million, 3.5 million, 4 million, 4.5 million, 5 million, or any number therein.
[0060] In some embodiments, the weight average molecular weight of the second fluorine-containing polymer is not more than 600,000. In some embodiments, the weight average molecular weight of the second fluorine-containing polymer is optionally 5,000, 10,000, 20,000, 30,000, 40,000, 50,000, 60,000, 70,000, 80,000, 90,000, 100,000, 110,000, 120,000, 130,000, 140,000, 150,000, 200,000, 250,000, 300,000, 350,000, 400,000, 450,000, 500,000, 550,000, 600,000, or any number therein.
[0061] In this application, the weight average molecular weight of the fluorine-containing polymer can be tested by selecting a method known in the art, for example, by adopting a gel chromatography method, for example, by adopting a Waters 2695 Isocratic HPLC type gel chromatograph (differential refractive index detector 2141) to test. In some embodiments, the test method is to take a polystyrene solution sample with a mass fraction of 3.0% as the standard and select a matching chromatographic column (oil-based: Styragel HT5DMF7.8*300 mm+Styragel HT4). Prepare a 3.0% polymer glue solution with purified N-methylpyrrolidone (NMP) solvent, and leave the prepared solution for one day to prepare for use. During the test, first draw tetrahydrofuran into the syringe, wash, and repeat several times. Then draw 5 ml of the experimental solution, eliminate the air in the syringe, and wipe the needle tip to dry. Finally, slowly inject the sample solution into the injection port. When the displayed value becomes stable, the data is acquired and the weight average molecular weight is read.
[0062] The fluorine element contained in the first fluorine-containing polymer and the second fluorine-containing polymer can form hydrogen bonds with hydroxyl groups and / or carboxyl groups on the active material surface and the current collector surface to improve the adhesive strength of the electrode plate. The first fluorine-containing polymer, which has a weight-average molecular weight of 1.5 million to 5 million, can improve the adhesive strength of the electrode plate at a low level of addition, and can improve the capacity retention rate during the cycle process of the battery. By adding the second fluorine-containing polymer to the adhesive, the crystallinity of the adhesive can be reduced, the flexibility of the electrode plate can be improved, the processing performance of the slurry can be further improved, and the delamination phenomenon does not occur in the electrode plate during the drying process of manufacturing the electrode plate, the uniformity of the dispersion of the active material in the electrode plate can be improved, the diaphragm resistance can be reduced, and the cycle performance of the battery can be further optimized. The above adhesive composition can ensure that the electrode plate has sufficient adhesive strength and flexibility at a low addition amount, which is advantageous for improving the energy density and cycle performance of the battery.
[0063] In some embodiments, the mass content of the second fluorine-containing polymer is 0.1% to 10%, based on the total mass of the adhesive composition.
[0064] In some embodiments, the mass content of the second fluorine-containing polymer, based on the total mass of the adhesive composition, is optionally 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, or any number therein.
[0065] If the mass ratio of the first fluorine-containing polymer to the second fluorine-containing polymer is too large, i.e., the mass of the first fluorine-containing polymer is too high, the purpose of reducing costs cannot be achieved; if the mass ratio of the first fluorine-containing polymer to the second fluorine-containing polymer is too small, i.e., the mass of the first fluorine-containing polymer is too low, the adhesion of the electrode plates is reduced, which affects the cycle performance of the battery.
[0066] By controlling the mass ratio of the first fluorine-containing polymer to the second fluorine-containing polymer within an appropriate range, the adhesive can have excellent adhesive strength to the electrode plate even at a low addition amount, and can improve the capacity retention rate during the cycle process of the battery. By adding a small amount of the second fluorine-containing polymer to the first fluorine-containing polymer, the crystallinity and processability of the adhesive can be effectively improved, and the manufacturing cost can be reduced while the cycle performance of the battery can be further improved.
[0067] In some embodiments, the adhesive composition has a crystallinity of less than 45%, optionally between 15%-45%.
[0068] As used herein, the term "crystallinity" refers to the proportion of crystalline regions in a polymer, and in the microstructure there are regions having some molecules that are stably arranged in an orderly fashion, and the regions in which the molecules are closely and regularly arranged are referred to as crystalline regions.
[0069] In the present application, the crystallinity test can be performed by selecting a method known in the art, for example, by adopting differential scanning calorimetry.In some embodiments, 0.5g of fluorine-containing polymer composition is placed in an aluminum crucible, flattened, the crucible is covered with a lid, and the test is performed in a nitrogen gas atmosphere, with a purge gas of 50 ml / min, a protective gas of 70 ml / min, a heating rate of 10 ° C / min, and a test temperature range of -100 ° C - 400 ° C, using a differential scanning calorimeter (DSC) of US TA Instrument Model Discovery 250, to remove thermal history.
[0070] In this test, the temperature change curve of DSC / (Mw / mg) of the fluorine-containing polymer composition is obtained and integrated, and the peak area is the melting enthalpy ΔH (J / g) of the fluorine-containing polymer composition, and the adhesive crystallinity=ΔH / (ΔHm)×100%, where ΔHm is the standard melting enthalpy (crystallization heat of fusion) of the fluorine-containing polymer, and ΔHm=104.7 J / g.
[0071] By adding the second fluorine-containing polymer to the first fluorine-containing polymer, the crystallinity of the adhesive can be effectively reduced and the flexibility of the electrode plate can be improved.
[0072] In some embodiments, the first fluorine-containing polymer comprises structural units derived from vinylidene fluoride. In some embodiments, the first fluorine-containing polymer is a vinylidene fluoride homopolymer. In some embodiments, the first fluorine-containing polymer is a vinylidene fluoride copolymer.
[0073] In some embodiments, the first fluorine-containing polymer further comprises a structural unit according to formula I: [ka] Here, R1 includes one or more of hydrogen, fluorine, chlorine, and trifluoromethyl groups.
[0074] In some embodiments, the first fluorine-containing polymer comprises one or more of polyvinylidene fluoride, vinylidene fluoride-trifluorochloroethylene copolymer, vinylidene fluoride-hexafluoropropylene copolymer, vinylidene fluoride-trifluorochloroethylene-hexafluoropropylene copolymer, vinylidene fluoride-tetrafluoroethylene-hexafluoropropylene copolymer, and vinylidene fluoride-trifluorochloroethylene-tetrafluoroethylene-hexafluoropropylene copolymer.
[0075] In some embodiments, the polydispersity coefficient of the first fluorine-containing polymer is 1.5 to 2.5, and optionally 2 to 2.3. In some embodiments, the polydispersity coefficient of the first fluorine-containing polymer is optionally 1.5, 1.6, 1.7, 1.8, 1.9, 2, 2.1, 2.2, 2.3, or any number therein.
[0076] As used herein, the term "polydispersity coefficient" is the ratio of the weight average molecular weight of a polymer to the number average molecular weight of the polymer.
[0077] As used herein, the term "number average molecular weight" is the sum of the products of the mole fractions occupied by molecules of different molecular weights in a polymer and the corresponding molecular weights.
[0078] If the polydispersity coefficient of the first fluorine-containing polymer is too large, the polymerization degree of the first fluorine-containing polymer will be relatively dispersed, which will affect the uniformity of the adhesive, and the adhesive will not be able to uniformly adhere the positive electrode active material to the current collector, which will affect the cycle performance of the battery and reduce the solid content of the slurry, making it impossible to further improve the energy density of the battery. If the polydispersity coefficient of the first fluorine-containing polymer is too small, the manufacturing process will be more difficult, the yield will be relatively low, and the production cost will be relatively high.
[0079] By setting the polydispersity coefficient of the first fluorine-containing polymer within a suitable range, the electrode plate has excellent adhesion and the capacity retention rate during the cycle process of the battery can be improved, and the suitable polydispersity coefficient of the first fluorine-containing polymer can effectively increase the solid content of the slurry and reduce the production cost.
[0080] In this application, the polydispersity coefficient of the first fluorine-containing polymer can be tested by selecting a method known in the art, for example, by adopting a gel chromatography method, for example, by adopting a Waters 2695 Isocratic HPLC type gel chromatograph (differential refractive index detector 2141). In some embodiments, a polystyrene solution sample with a mass fraction of 3.0% is used as a reference, and a matching chromatographic column (oil-based: Styragel HT5DMF7.8*300mm+Styragel HT4) is selected. A 3.0% adhesive glue solution is prepared with purified N-methylpyrrolidone (NMP) solvent, and the prepared solution is left to stand for one day for use. During the test, first, tetrahydrofuran is sucked into a syringe, washed, and repeated several times. Then, 5 ml of the experimental solution is sucked, the air in the syringe is removed, and the needle tip is wiped and dried. Finally, the sample solution is slowly injected into the injection port. When the display value becomes stable, data is acquired. The weight average molecular weight a and number average molecular weight b are read off. The polydispersity coefficient = a / b.
[0081] In some embodiments, the crystallinity of the first fluorine-containing polymer is 34% to 48%. In some embodiments, the crystallinity of the first fluorine-containing polymer is 40% to 48%. In some embodiments, the crystallinity of the first fluorine-containing polymer is 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, and any number therein.
[0082] In some embodiments, the viscosity of a glue solution containing the first fluorine-containing polymer with a mass content of 4% produced by dissolving the first fluorine-containing polymer in N-methylpyrrolidone is 2400 mPa·s to 5000 mPa·s. In some embodiments, the viscosity of the glue solution containing the first fluorine-containing polymer having a mass content of 4% produced by dissolving the first fluorine-containing polymer in N-methylpyrrolidone is optionally 2500 mPa·s to 3000 mPa·s, 3000 mPa·s to 3300 mPa·s, 3300 mPa·s to 3500 mPa·s, 3500 mPa·s to 3800 mPa·s, 3800 mPa·s to 4000 mPa·s, 4000 mPa·s to 4200 mPa·s, 4200 mPa·s to 4600 mPa·s, 4600 mPa·s to 5000 mPa·s, 3100 mPa·s to 3400 mPa·s, 3400 mPa·s to 3800 mPa·s, 38 ...4700 mPa·s to 5000 mPa·s, 4700 mPa·s to 5000 mPa·s, 4700 mPa·s to 5000 mPa·s, 4700 mPa·s to 5000 mPa·s, 4700 mPa·s to 5000 mPa·s, 4700 mPa·s to 5000 mPa·s, 4700 mPa·s to 5000 mPa·s, mPa·s~5000 mPa·s, 3600 mPa·s~5000 mPa·s.
[0083] If the viscosity of the first fluorine-containing polymer is too high, the viscosity of the adhesive solution produced will be too high, making it difficult to stir and reducing the dispersibility of the adhesive, making it difficult for the adhesive to uniformly adhere the positive active material to the current collector, which will affect the cycle performance of the battery and also reduce the viscosity of the adhesive solution, reducing the speed of the slurry production process. If the viscosity of the first fluorine-containing polymer is too low, the viscosity of the adhesive solution produced will be too low, making it difficult for the electrode plate to have sufficient adhesive strength even at a low addition amount.
[0084] In addition, when preparing the positive electrode slurry, the adhesive must have a certain viscosity to prevent the precipitation of the positive electrode active material and auxiliary agents such as the conductive agent and to allow the slurry to be placed relatively stably. In the prior art, in order to achieve a viscosity of the glue solution of 2400 mPa·s to 5000 mPa·s, it is necessary to contain an adhesive whose mass content is at least 7% based on the mass of the glue solution, but the first fluorine-containing polymer of the present application can achieve the expected viscosity of the glue solution with a usage amount of 4%, providing a basis for reducing the content of the adhesive in the positive electrode membrane layer.
[0085] By controlling the viscosity of the first fluorine-containing polymer solution within an appropriate range, the electrode plate can have excellent adhesive performance even with a low additive amount of adhesive, and the capacity retention rate during the cycle process of the battery can be improved.
[0086] In some embodiments, the second fluorine-containing polymer comprises structural units according to formula II: [ka] Here, R2 and R3 each independently represent a hydrogen atom, a halogen atom, or a C group containing at least one fluorine atom. 1-3 and at least one alkyl group.
[0087] In some embodiments, R2, R3 each independently comprise at least one of hydrogen, fluorine, chlorine, or a trifluoromethyl group.
[0088] In some embodiments, the second fluorine-containing polymer comprises one of polytetrafluoroethylene, polyvinylidene fluoride, poly(vinylidene fluoride-hexafluoropropylene) copolymer, poly(vinylidene fluoride-tetrafluoroethylene) copolymer, poly(vinylidene fluoride-fluorochloroethylene) copolymer, and poly(vinylidene fluoride-tetrafluoroethylene-hexafluoropropylene) copolymer.
[0089] In some embodiments, the end groups of the second fluorine-containing polymer contain hydroxyl or ester groups.
[0090] The second fluorine-containing polymer has a small weight average molecular weight and a high mass content of end group, so the end group has a relatively large effect on the performance of the second fluorine-containing polymer.The end group of the second fluorine-containing polymer contains a hydroxyl group or an ester group, which can effectively improve the adhesion of the second fluorine-containing polymer and reduce the decrease in the plate adhesion performance caused by adding the second fluorine-containing polymer.
[0091] The end group structure of the polymer can be studied by nuclear magnetic resonance techniques. 19 F-NMR and 1 The end group structure of the polymer can be analyzed by H-NMR. For example, dimethylsulfoxide is used as the solvent, CFCl3 is used as the fluorine spectrum standard, and TMS is used as the hydrogen spectrum standard.
[0092] In one embodiment of the present application, there is provided a method for producing an adhesive composition, the method comprising the steps of: Production of a first fluorine-containing polymer: A first polymerization reaction is carried out on a raw material containing a vinylidene fluoride monomer under polymerization conditions to produce a first fluorine-containing polymer, and the weight average molecular weight of the first fluorine-containing polymer is 1.5 million to 5 million; Preparation of a second fluorine-containing polymer: carrying out a second polymerization reaction on a raw material containing vinylidene fluoride monomer under polymerization conditions to prepare a second fluorine-containing polymer, and the weight average molecular weight of the second fluorine-containing polymer is not more than 600,000; Blending: A first fluorine-containing polymer is blended with a second fluorine-containing polymer to produce an adhesive composition.
[0093] As used herein, the term "blending" refers to the process of producing two or more substances as a macroscopically homogeneous material under certain conditions such as temperature and / or shear stress.
[0094] The adhesive manufacturing method is simple, environmentally friendly, reduces costs, and is favorable for industrial production. At the same time, the adhesive manufactured by this method can provide excellent adhesion to the electrode plate and improve the capacity retention rate during the cycling process of the battery even with a small amount of additive.
[0095] In some embodiments, in the blending step, the mass ratio of the first fluorine-containing polymer to the second fluorine-containing polymer is 999: 1 to 9: 1. In some embodiments, the mass ratio of the first fluorine-containing polymer to the second fluorine-containing polymer is optionally 9: 1, 20: 1, 30: 1, 40: 1, 50: 1, 60: 1, 70: 1, 80: 1, 90: 1, 100: 1, 200: 1, 300: 1, 400: 1, 500: 1, 600: 1, 700: 1, 800: 1, 900: 1, 999: 1, or any value therein.
[0096] By controlling the mass ratio of the first fluorine-containing polymer to the second fluorine-containing polymer within an appropriate range, the adhesive can have excellent adhesive strength to the electrode plate even at a low addition amount, and can improve the processability of the battery.
[0097] In some embodiments, the synthesis step of the first fluorine-containing polymer includes carrying out a first polymerization reaction for 6 h to 12 h in a non-reactive gas atmosphere with a raw material including a vinylidene fluoride monomer under a reaction pressure of 6 MPa to 8 MPa and a reaction temperature of 45° C. to 60° C.; The method includes adding a chain transfer agent, lowering the pressure in the reaction system to 2 MPa to 2.5 MPa, stopping the reaction, and performing solid-liquid separation to leave a solid phase.
[0098] As used herein, the term "non-reactive gas" refers to a gas that does not react with the reactants in a reaction system; common non-reactive gases are inert gases such as argon gas and nitrogen gas.
[0099] In some embodiments, the reaction pressure of the first polymerization reaction is one of 6 MPa to 6.5 MPa, 6.5 MPa to 7 MPa, 7 MPa to 7.5 MPa, 7.5 MPa to 8 MPa, 6 MPa to 7 MPa, and 7 MPa to 8 MPa.
[0100] In some embodiments, the reaction temperature of the first polymerization reaction is one of 45°C to 50°C, 50°C to 55°C, 55°C to 60°C, 45°C to 55°C, or 50°C to 60°C.
[0101] In some embodiments, the time period for the first polymerization reaction is one of 6h to 7h, 7h to 8h, 8h to 9h, 9h to 10h, 10h to 11h, 11h to 12h, 6h to 8h, or 6h to 10h.
[0102] When the polymerization reaction pressure is relatively large, the pressure at which the monomer enters the reaction solution is relatively large, and the monomer enters the reaction solution in large quantities, causing a large-scale polymerization reaction to occur, and the number of first fluorine-containing polymers produced is large, and the polydispersity coefficient is large; with the decrease in monomer, the polymerization reaction will be insufficient in the supply of monomer, and the weight-average molecular weight of the first fluorine-containing polymer produced will be relatively small, which will affect the adhesion of the electrode plate and the cycle capacity retention rate of the battery.
[0103] When the polymerization reaction pressure is relatively low, the pressure at which the monomer enters the reaction solution is relatively low, and the reaction monomer cannot be continuously replenished, which is unfavorable to the continuous progress of the polymerization, and the weight-average molecular weight of the first fluorine-containing polymer produced is too low to meet the requirements for adhesive strength, and the cycle performance of the battery is also somewhat reduced.
[0104] When the polymerization reaction temperature is low, the promotion force of copolymerization is relatively small, the polymerization reaction is insufficient, and the molecular weight of the first fluorine-containing polymer produced is small, the adhesive strength is greatly reduced, and the cycle performance is obviously reduced.
[0105] When the polymerization reaction temperature is high, a large-scale polymerization reaction occurs, so that the number of first fluorine-containing polymers produced is large, and with the decrease of monomer, the polymerization reaction causes an insufficient supply of monomer, so that the weight-average molecular weight of the produced first fluorine-containing polymer is relatively small, which affects the adhesive strength of the electrode plate and the cycle capacity retention rate of the battery.
[0106] If the polymerization reaction time is short, the polymerization reaction cannot be continued, and the weight average molecular weight of the first fluorine-containing polymer produced is small, which also leads to deterioration of the adhesive strength and cycle performance.
[0107] If the polymerization reaction time is long, the polymerization conditions will no longer be achieved due to continuous consumption of monomer and reduction of pressure, and the polymerization reaction cannot be continued even if the reaction time is extended, resulting in a decrease in production efficiency.
[0108] By controlling the reaction pressure, reaction temperature and reaction time of the polymerization reaction within appropriate ranges, the weight average molecular weight of the first fluorine-containing polymer can be controlled, the electrode plate can have excellent adhesive strength, and the battery can have a relatively good cycle capacity retention rate during the cycle process.
[0109] In some embodiments, the first polymerization reaction comprises: adding a solvent and a dispersant to a vessel, drawing a vacuum on the vessel and then filling the vessel with a non-reactive gas; Adding a first initiator and a pH adjusting agent to the vessel, adjusting the pH value to 6.5-7, and adding a raw material containing vinylidene fluoride monomer, and making the pressure in the vessel 6MPa-8MPa; and then stirring for 30 to 60 minutes, followed by raising the temperature to 45° C. to 60° C. to carry out a first polymerization reaction.
[0110] By first homogeneously mixing the materials before carrying out the first polymerization reaction at elevated temperature, the reaction can be more thorough and the resulting polymer will have more suitable polydispersity index, crystallinity and particle size.
[0111] In some embodiments, the amount of the solvent used in the first polymerization reaction is 2 to 8 times the mass of the vinylidene fluoride monomer. The amount of the solvent used may be, for example, 3, 4, 5, 6, or 7 times the mass of the vinylidene fluoride monomer. In some embodiments, the solvent is a water solvent.
[0112] In some embodiments, the dispersing agent comprises one or more of a cellulose ether and a polyvinyl alcohol.
[0113] In some embodiments, the cellulose ether comprises one or more of a methyl cellulose ether and a carboxyethyl cellulose ether.
[0114] In some embodiments, the amount of dispersant used in the first polymerization reaction is 0.1% to 0.3% of the vinylidene fluoride monomer mass, and may even be, for example, 0.2% of the vinylidene fluoride monomer mass.
[0115] In some embodiments, the first initiator is an organic peroxide, which in some embodiments includes one or more of tert-amyl peroxypivalate, tert-amyl peroxypivalate, 2-ethyl peroxydicarbonate, diisopropyl peroxydicarbonate, and tert-butyl peroxypivalate.
[0116] In some embodiments, the amount of the first initiator used is 0.15% to 1% of the total monomer mass. The amount of the first initiator used may further be, for example, 0.2%, 0.4%, 0.6%, or 0.8% of the total monomer mass.
[0117] In some embodiments, the pH adjuster comprises one or more of potassium carbonate, potassium bicarbonate, sodium carbonate, sodium bicarbonate, and aqueous ammonia.
[0118] In some embodiments, the amount of pH adjuster used is between 0.05% and 0.2% of the vinylidene fluoride monomer mass. The amount of pH adjuster used may, for example, even be 0.1% or 0.15% of the vinylidene fluoride monomer mass.
[0119] In some embodiments, the chain transfer agent comprises one or more of cyclohexane, isopropyl alcohol, methanol, and acetone.
[0120] In some embodiments, the amount of chain transfer agent used in the first polymerization reaction is 1.5% to 3% of the mass of vinylidene fluoride monomer, and the amount of chain transfer agent used may be, for example, 2% or 2.5%. By controlling the amount of chain transfer agent used within an appropriate range, the chain length of the first fluorine-containing polymer can be controlled, thereby obtaining a first fluorine-containing polymer with an appropriate weight average molecular weight range.
[0121] In some embodiments, the second method for producing a fluorine-containing polymer comprises the steps of: The method includes carrying out a polymerization reaction of at least one monomer represented by formula III in a non-reactive gas atmosphere at 0.1-5 MPa and a reaction temperature of 60°C to 90°C for 0.5 hours to 8 hours, terminating the reaction, and performing solid-liquid separation to leave a solid phase to obtain a second fluorine-containing polymer; [ka] Here, R4 and R5 each independently represent a hydrogen atom, a halogen atom, or a C group containing at least one fluorine atom. 1-3 and at least one alkyl group.
[0122] In some embodiments, the reaction pressure of the second polymerization reaction is 0.1 MPa, 1 MPa, 2 MPa, 3 MPa, 4 MPa, 5 MPa, or any value therein.
[0123] In some embodiments, the reaction temperature of the second polymerization reaction is 60° C., 65° C., 70° C., 75° C., 80° C., 85° C., 90° C., or any value therein.
[0124] By carrying out the polymerization reaction at high temperature and pressure, it is possible to improve the reaction efficiency, shorten the reaction time, increase the reaction conversion rate, and improve the uniformity and purity of the product.
[0125] In some embodiments, the second polymerization reaction comprises: adding a solvent and a dispersant to a vessel and filling said vessel with a non-reactive gas; The method further includes the steps of adding the monomer represented by formula III, raising the temperature to 60° C. to 90° C., and then adding a second initiator and a chain transfer agent.
[0126] In some embodiments, the second initiator comprises an inorganic peroxide and may be selected from potassium persulfate or ammonium persulfate.
[0127] According to the nuclear magnetic results, when inorganic peroxide is used as initiator, the end group of the second fluorine-containing polymer includes -CF2-CH2OH or -CF2-CH2OOCCH3. The presence of hydroxyl group and ester group in the end group can effectively improve the adhesion of the second fluorine-containing polymer, and reduce the deterioration of the adhesive performance of the adhesive composition caused by its addition.
[0128] In some embodiments, the weight content of the initiator is 3%-12%, based on the total weight of the monomers of formula III.
[0129] High initiator content contributes to improving reaction efficiency, reducing reaction time, and improving product uniformity.
[0130] In some embodiments, the chain transfer agent comprises one or more of cyclohexane, isopropyl alcohol, methanol, and acetone.
[0131] [Positive electrode plate] The positive electrode plate includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, the positive electrode film layer including a positive electrode active material, a conductive agent, and an adhesive according to some embodiments or an adhesive produced by a manufacturing method according to some embodiments.
[0132] This positive electrode plate has excellent adhesive strength even with a low amount of adhesive added.
[0133] In some embodiments, the mass fraction of the adhesive composition does not exceed 1.2%, based on the total mass of the positive electrode membrane layer.
[0134] In some embodiments, the weight fraction of the adhesive is between 0.8% and 1.2%, hi some embodiments, the weight content of the adhesive is 0.8%, 0.9%, 1%, 1.1%, 1.2%, or any value therein.
[0135] The adhesive composition can effectively improve the adhesive performance of the electrode plate even in a small amount, and the electrode plate has excellent flexibility and processability, so that the battery has high energy density and cycle performance.
[0136] In some embodiments, the positive electrode active material is a lithium-containing transition metal oxide.
[0137] In some embodiments, the positive electrode active material is at least one of lithium iron phosphate or lithium nickel cobalt manganese oxide, or doped modifications thereof, or conductive carbon-coated, conductive metal-coated, or conductive polymer-coated modifications thereof.
[0138] In some embodiments, a method for manufacturing a positive electrode plate is provided, the method including the steps of:
[0139] First step: A positive electrode active material, a conductive agent, and an adhesive according to any one of the embodiments or an adhesive produced by the production method according to any one of the embodiments are mixed together, and a first stirring is performed.
[0140] Second step: A solvent is added and a second stirring is carried out.
[0141] Third stage: Add a dispersant and perform the third stirring to obtain a slurry, and control the slurry viscosity to 8000 mpa·s~15000 mpa·s.
[0142] Fourth step: The slurry is applied onto a positive electrode current collector to obtain a positive electrode plate.
[0143] This preparation method is simple and advantageous for industrial production. This preparation method is advantageous for reducing sedimentation in the slurry of the high molecular weight first fluorine-containing polymer, and contributes to improving the quality of the slurry and the uniformity of the positive electrode plate.
[0144] In some embodiments, in the first stirring, the stirring revolution speed is 25 r / min and the stirring time is 30 min.
[0145] In some embodiments, in the second stirring, the revolution speed of the stirring is 25 r / min, the rotation speed of the stirring is 800 to 1000 r / min, and the stirring time is 50 to 80 min.
[0146] In some embodiments, in the third stirring, the rotation speed of the stirring is 1200 to 1500 r / min, and the stirring time is 50 to 70 min.
[0147] In some embodiments, the dispersing agent is at least one of polyethylene glycol octylphenyl ether, polyvinylpyrrolidone, polyvinyl alcohol, carboxymethyl cellulose, polyacrylamide, polyacrylic acid, sodium polyacrylate, polyacetimide.
[0148] In some embodiments, the mass fraction of the dispersant is between 0.2% and 0.5%, based on the total mass of the positive electrode membrane layer.
[0149] In some embodiments, the positive electrode current collector may be a metal foil sheet or a composite current collector. For example, an aluminum foil may be used as the metal foil sheet. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer base layer. The composite current collector may be formed by forming a metal material (such as aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0150] In some embodiments, the positive electrode active material may be a positive electrode active material used in batteries known in the art. For example, the positive electrode active material may include at least one of lithium-containing phosphates with an olivine structure, lithium transition metal oxides, and their respective modified compounds. However, the present application is not limited to these materials, and other conventional materials that can be used as positive electrode active materials in batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Here, examples of the lithium transition metal oxide include lithium cobalt oxide (e.g., LiCoO2), lithium nickel oxide (e.g., LiNiO2), lithium manganese oxide (e.g., LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (e.g., LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM 333 (may be abbreviated as LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM 523 (may be abbreviated as LiNi 0.5 Co 0.25 Mn 0.25 O2(NCM 211 (may be abbreviated as LiNi 0.6 Co 0.2 Mn0.2 O2(NCM 622 (may be abbreviated as LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM 811 Lithium nickel cobalt aluminum oxide (e.g., LiNi 0.85 Co 0.15 Al 0.05 Examples of the lithium-containing phosphate having an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (e.g., LiFePO4 (which may be abbreviated as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (e.g., LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium manganese iron phosphate, and a composite material of lithium manganese iron phosphate and carbon.
[0151] In some embodiments, the positive electrode film layer further optionally includes a conductive agent, which may include at least one of superconducting carbon, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0152] In some embodiments, the positive electrode plate can be manufactured in the following manner: The components for manufacturing the positive electrode plate, such as the positive electrode active material, the conductive agent, the adhesive, and any other components, are dispersed in a solvent (e.g., N-methylpyrrolidone) to form a positive electrode slurry, which is then coated on a positive electrode current collector, and the positive electrode plate is obtained after processes such as drying and cold pressing.
[0153] [Negative electrode plate] The negative electrode plate includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, the negative electrode film layer including a negative electrode active material.
[0154] For example, the negative electrode current collector has two opposing surfaces in the thickness direction of the negative electrode current collector, and the negative electrode film layer is disposed on either one or both of the two opposing surfaces of the negative electrode current collector.
[0155] In some embodiments, the negative electrode current collector may be a metal foil sheet or a composite current collector. For example, the metal foil sheet may be a copper foil. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (such as copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0156] In some embodiments, the negative electrode active material may be a negative electrode active material for batteries known in the art. For example, the negative electrode active material may include at least one of artificial graphite, natural graphite, soft carbon, hard carbon, silicone-based material, tin-based material, and lithium titanate. The silicone-based material may be selected from at least one of silicone, silicone oxide, silicone carbon composite, silicone nitrogen composite, and silicone alloy. The tin-based material may be selected from at least one of tin, tin oxide, and tin alloy. However, the present application is not limited to these materials, and other conventional materials that can be used as a battery negative electrode active material may be used. These negative electrode active materials may be used alone or in combination of two or more.
[0157] In some embodiments, the negative electrode membrane layer further optionally comprises an adhesive, which may be selected from at least one of styrene butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0158] In some embodiments, the negative electrode film layer further optionally comprises a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0159] In some embodiments, the negative electrode membrane layer optionally further comprises other auxiliary agents, such as a thickening agent (eg, sodium carboxymethylcellulose (CMC-Na)).
[0160] In some embodiments, the negative electrode plate can be manufactured in the following manner: Components for manufacturing the negative electrode plate, such as a negative electrode active material, a conductive agent, an adhesive, and any other components, are dispersed in a solvent (e.g., deionized water) to form a negative electrode slurry, which is then coated on a negative electrode current collector, and the negative electrode plate is obtained after processes such as drying and cold pressing.
[0161] [Electrolyte] The electrolyte serves to conduct ions between the positive and negative electrodes. The present application is not specifically limited to the type of electrolyte, which can be selected according to need. For example, the electrolyte may be liquid, gel, or all solid.
[0162] In some embodiments, the electrolyte is an electrolytic solution, the electrolytic solution including an electrolyte salt and a solvent.
[0163] In some embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonate), lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluoro(oxalato)borate, lithium bis(oxalato)borate, lithium difluorobis(oxalato)phosphate, and lithium tetrafluoro(oxalato)phosphate.
[0164] In some embodiments, the solvent may be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, ethyl methyl sulfone, and diethyl sulfone.
[0165] In some embodiments, the electrolyte solution may further include optional additives, for example, additives for forming a negative electrode film, additives for forming a positive electrode film, and additives for improving some performance of the battery, such as additives for improving the overcharge performance of the battery, additives for improving the high temperature or low temperature performance of the battery, etc.
[0166] [Separator] In some embodiments, the secondary battery further includes a separator. The present application is not particularly limited to the type of separator, and any known porous structure separator having good chemical stability and mechanical stability may be selected.
[0167] In some embodiments, the material of the separator may be at least one selected from glass fiber, nonwoven fabric, polyethylene, polypropylene, and fluorine-containing polymers. The separator may be a monolayer film or a multilayer composite film, and there is no particular limitation. When the separator is a multilayer composite film, the materials of each layer may be the same or different, and there is no particular limitation.
[0168] In some embodiments, the positive plates, negative plates and separators can be fabricated into an electrode assembly by a winding process or a lamination process.
[0169] In some embodiments, the secondary battery may include an exterior body, which may be used to package the electrode assembly and the electrolyte.
[0170] In some embodiments, the exterior of the secondary battery may be a hard case, such as a hard plastic case, an aluminum case, a steel case, etc. The exterior of the secondary battery may be a pouch, such as a bag-shaped pouch. The material of the pouch may be plastic, such as polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0171] The present application is not particularly limited to the shape of the secondary battery, which may be cylindrical, rectangular, or any other shape. For example, FIG. 1 shows a secondary battery 5 with a rectangular structure as an example.
[0172] In some embodiments, referring to FIG. 2, the exterior body may include a case 51 and a cover plate 53. Here, the case 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate surround and form a receiving cavity. The case 51 has an opening communicating with the receiving cavity, and the cover plate 53 can cover the opening to seal the receiving cavity. The positive electrode plate, the negative electrode plate and the separator can form an electrode assembly 52 by a winding process or a stacking process. The electrode assembly 52 is packaged in the receiving cavity. An electrolyte is infiltrated into the electrode assembly 52. The number of electrode assemblies 52 included in the secondary battery 5 may be one or more, and those skilled in the art can select it according to the actual needs.
[0173] In some embodiments, the secondary batteries may be assembled into a battery module, and the number of secondary batteries included in the battery module may be one or more, with the specific number being selectable by one skilled in the art depending on the application and capacity of the battery module.
[0174] Fig. 3 shows an example of a battery module 4. Referring to Fig. 3, in the battery module 4, the multiple secondary batteries 5 may be arranged in sequence along the longitudinal direction of the battery module 4. Of course, they may be arranged in any other manner. Furthermore, the multiple secondary batteries 5 may be fixed by fasteners.
[0175] Optionally, the battery module 4 may further include a housing having an accommodating space, and the multiple secondary batteries 5 are accommodated in the accommodating space.
[0176] In some embodiments, the battery modules may be further assembled into a battery pack, and the number of battery modules included in the battery pack may be one or more, and the specific number can be selected by one skilled in the art according to the application and capacity of the battery pack.
[0177] 4 and 5 show an example of a battery pack 1. Referring to Fig. 4 and Fig. 5, the battery pack 1 may include a battery box and a plurality of battery modules 4 installed in the battery box. The battery box may include an upper housing 2 and a lower housing 3, and the upper housing 2 may cover the lower housing 3 to form a sealed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the battery box in any manner.
[0178] The present application further provides a power consuming device, the power consuming device including at least one of the secondary battery, the battery module, or the battery pack according to the present application. The secondary battery, the battery module, or the battery pack may be used as a power source for the power consuming device, or may be used as an energy storage unit for the power consuming device. The power consuming device may include, but is not limited to, a mobile device (e.g., a mobile phone, a laptop, etc.), an electric vehicle (e.g., a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship, a satellite, an energy storage system, etc.
[0179] The power consumption device can be a secondary battery, a battery module, or a battery pack depending on its usage demand.
[0180] 6 shows an example of a power consumption device, such as a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. A battery pack or a battery module can be employed to meet the demand for high power output and high energy density of the secondary battery of the power consumption device.
[0181] Other example devices may be mobile phones, tablet computers, notebook computers, etc. These devices generally require thinness and can employ secondary batteries as their power source.
[0182] 1. Example The following is a description of the examples of the present application. The examples described below are illustrative and are only used to interpret the present application, and should not be understood as limitations to the present application. If no specific techniques or conditions are specified in the examples, they are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. If no manufacturer is specified, the reagents or instruments used are all commercially available ordinary products.
[0183] Example 1 1) Production of adhesive composition Preparation of first fluorine-containing polymer: add 4kg deionized water and 2g methyl cellulose ether into 10L autoclave, evacuate and replace O2 with N2 three times, add 5g tert-butyl peroxypivalate and 2g sodium bicarbonate again, add 1Kg vinylidene fluoride monomer, and reach pressure of 7MPa, mix and stir for 30min, heat to 45℃, carry out polymerization reaction, add 20g cyclohexane after polymerization reaction for 10h, continue reaction, stop reaction when pressure in reactor drops to 2MPa, centrifuge reaction system, collect solid phase, wash and dry to obtain polyvinylidene fluoride adhesive with weight average molecular weight of 3.2 million, that is, first fluorine-containing polymer.
[0184] Polyvinylidene fluoride adhesive with a weight average molecular weight of 3.2 million has a polydispersity coefficient of 2.2, a crystallinity of 45%, and a Dv50 particle size of 100 μm. It was dissolved in an N-methylpyrrolidone solution to prepare a 4 wt% solution, and the measured viscosity of the solution was 4900 mPa s.
[0185] Preparation of the second fluorine-containing polymer: In a 0.5L autoclave, 219g of deionized water and 0.1g of hydroxypropyl methylcellulose were added, and the atmosphere was replaced with nitrogen gas several times to remove oxygen, after which 120g of vinylidene fluoride monomer gas was added. After the monomer was added, the reaction temperature was controlled at 85°C, and after adding 0.14g of water-soluble ammonium persulfate initiator and isopropyl alcohol chain transfer agent, the reaction was started, the amount of initiator added was about 8% of the total amount of monomer added, the polymerization reaction time was 1h, and the pressure was maintained at 4.4MPa. After the reaction product was washed with water and dried, a polyvinylidene fluoride polymer was obtained.
[0186] The first fluorine-containing polymer and the second fluorine-containing polymer were blended to obtain an adhesive composition containing the first fluorine-containing polymer and the second vinylidene fluoride in a mass ratio of the first fluorine-containing polymer to the second fluorine-containing polymer of 99.9:0.1.
[0187] 2) Manufacturing of positive electrode plates Lithium iron phosphate, an adhesive composition, and acetylene black are stirred in a planetary stirring tank at a revolution speed of 25 r / min for 30 min, where the mass fraction of the adhesive composition is 1.2% based on the total mass of the positive electrode film layer; Add 2.4 kg of N-methylpyrrolidone (NMP) solution to the stirring tank and stir for 70 minutes at a revolution speed of 25 r / min and a rotation speed of 900 r / min. Add 12.3 g of polyvinylpyrrolidone dispersant to the stirring tank, and stir for 60 minutes at a revolution speed of 25 r / min and a rotation speed of 1300 r / min. After the stirring was finished, the slurry viscosity was tested and the viscosity was controlled at 8000-15000 mpa·s.
[0188] If the viscosity was high, an N-methylpyrrolidone (NMP) solution was added to reduce the viscosity to the above range, and after adding the NMP solution, the mixture was stirred for 30 minutes at a revolution speed of 25 r / min and a rotation speed of 1200 to 1500 r / min to obtain a positive electrode slurry. The produced positive electrode slurry was applied onto a carbon-coated aluminum foil, baked at 110°C for 15 minutes, cold pressed, and then cut into a ring shape with a diameter of 15 mm to obtain a positive electrode plate.
[0189] 3) Negative electrode plate A piece of metallic lithium served as the negative electrode plate.
[0190] 4) Separator A polypropylene membrane served as the separator.
[0191] 5) Electrolyte production In a glove box (H2O<0.1ppm, O2<0.1ppm) with an argon gas atmosphere, the organic solvents ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed uniformly in a volume ratio of 3 / 7, LiPF6 lithium salt was added and dissolved in the organic solvent, and the mixture was stirred uniformly to prepare a 1M LiPF6EC / EMC solution, thereby obtaining the electrolyte.
[0192] 6) Battery manufacturing The positive electrode plate, negative electrode plate, separator and electrolyte in Example 1 were assembled into a button cell box to form a button battery.
[0193] Examples 2-9 The mass ratio of the first fluorine-containing polymer to the second fluorine-containing polymer in the adhesive composition was adjusted, and the other manufacturing methods were the same as those in Example 1, and the specific parameters were as shown in Tables 1-6.
[0194] Examples 10-15 The weight average molecular weight of the second fluorine-containing polymer in the adhesive composition is adjusted, and other methods are the same as those in Example 3, and the specific parameters are as shown in Tables 1-6.
[0195] In Example 10, the weight average molecular weight of the polyvinylidene fluoride is 5,000, and the production method is as follows.
[0196] In a 0.5L autoclave, 219g of deionized water and 0.1g of hydroxypropyl methylcellulose were added, and the atmosphere was replaced with nitrogen gas several times to remove oxygen, after which 120g of vinylidene fluoride monomer gas was added. After the monomer was added, the reaction temperature was controlled at 87°C, and the reaction was started after adding 0.15g of water-soluble ammonium persulfate initiator and isopropyl alcohol chain transfer agent, and the amount of initiator added was about 8% of the total amount of monomer added. The polymerization reaction time was 0.8h, and the pressure was maintained at 4.4MPa. After the reaction product was washed with water and dried, a polyvinylidene fluoride polymer was obtained.
[0197] In Example 11, the weight average molecular weight of the polyvinylidene fluoride is 20,000, and the production method is as follows.
[0198] In a 0.5L autoclave, 219g of deionized water and 0.1g of hydroxypropyl methylcellulose were added, and the atmosphere was replaced with nitrogen gas several times to remove oxygen, after which 120g of vinylidene fluoride monomer gas was added. After the monomer was added, the reaction temperature was controlled at 83°C, and the reaction was started after adding 0.14g of water-soluble ammonium persulfate initiator and isopropyl alcohol chain transfer agent, and the amount of initiator added was about 8% of the total amount of monomer added. The polymerization reaction time was 1h, and the pressure was maintained at 4.4MPa. After the reaction product was washed with water and dried, polyvinylidene fluoride polymer was obtained.
[0199] In Example 12, the weight average molecular weight of the polyvinylidene fluoride is 80,000, and the production method is as follows.
[0200] In a 0.5L autoclave, 219g of deionized water and 0.1g of hydroxypropyl methylcellulose were added, and the atmosphere was replaced with nitrogen gas several times to remove oxygen, after which 120g of vinylidene fluoride monomer gas was added. After the monomer was added, the reaction temperature was controlled at 82°C, and the reaction was started after adding 0.12g of water-soluble ammonium persulfate initiator and isopropyl alcohol chain transfer agent, and the amount of initiator added was about 8% of the total amount of monomer added. The polymerization reaction time was 1.5h, and the pressure was maintained at 4.4MPa. After the reaction product was washed with water and dried, polyvinylidene fluoride polymer was obtained.
[0201] In Example 13, the weight average molecular weight of the polyvinylidene fluoride is 150,000, and the production method is as follows.
[0202] In a 0.5L autoclave, 219g of deionized water and 0.1g of hydroxypropyl methylcellulose were added, and the atmosphere was replaced with nitrogen gas several times to remove oxygen, after which 120g of vinylidene fluoride monomer gas was added. After the monomer was added, the reaction temperature was controlled at 79°C, and after adding 0.12g of water-soluble ammonium persulfate initiator and isopropyl alcohol chain transfer agent, the reaction was started, the amount of initiator added was about 7.0% of the total amount of monomer added, the polymerization reaction time was 1.5h, and the pressure was maintained at 4.4MPa. After the reaction product was washed with water and dried, a polyvinylidene fluoride polymer was obtained.
[0203] In Example 14, the weight average molecular weight of the polyvinylidene fluoride is 400,000, and in Example 15, the weight average molecular weight of the polyvinylidene fluoride is 600,000, both of which are commercially available.
[0204] Example 16 is basically the same as Example 3, except that the weight-average molecular weight of the first fluorine-containing polymer is 1.5 million. Example 17 is basically the same as Example 12, except that the weight-average molecular weight of the first fluorine-containing polymer is 1.5 million. Example 18 is basically the same as Example 14, except that the weight-average molecular weight of the first fluorine-containing polymer is 1.5 million. A method for producing polyvinylidene fluoride having a weight-average molecular weight of 1.5 million is as follows.
[0205] Add 4kg of deionized water and 2g of methylcellulose ether to a 10L autoclave, evacuate and replace O2 with N2 three times, add 5g of tert-butyl peroxypivalate and 2g of sodium bicarbonate again, add 1kg of vinylidene fluoride monomer, and make the pressure reach 7MPa. Mix and stir for 30min, heat to 45℃, and carry out polymerization reaction. After polymerization reaction for 5h, add 30g of cyclohexane to continue the reaction. When the pressure in the reactor drops to 2MPa, the reaction is stopped. After centrifuging the reaction system, the solid phase is collected, washed and dried to obtain.
[0206] This polyvinylidene fluoride has a polydispersity coefficient of 2.18, a crystallinity of 41.5%, and a Dv50 particle size of 45 μm. It was dissolved in an N-methylpyrrolidone solution to prepare a 4 wt% solution, and the measured viscosity of the solution was 3000 mPa s.
[0207] The preparation methods of Examples 19-21 are basically the same as those of Examples 16-18, except that the weight average molecular weight of the first fluorine-containing polymer is 5,000,000. The specific preparation methods are as follows:
[0208] Add 4kg of deionized water and 2g of methylcellulose ether to a 10L autoclave, evacuate and replace O2 with N2 three times, add 5g of tert-butyl peroxypivalate and 2g of sodium bicarbonate again, add 1kg of vinylidene fluoride monomer, and make the pressure reach 7MPa. Mix and stir for 30min, heat to 45℃, and carry out polymerization reaction. After polymerization reaction for 12h, add 15g of cyclohexane to continue the reaction. When the pressure in the reactor drops to 2MPa, the reaction is stopped. After centrifuging the reaction system, collect the solid phase, wash and dry to obtain.
[0209] This polyvinylidene fluoride has a polydispersity coefficient of 2.2, a crystallinity of 46%, and a Dv50 particle size of 150 μm. It was dissolved in an N-methylpyrrolidone solution to prepare a 4 wt% solution, and the measured viscosity of the solution was 6,500 mPa s.
[0210] The manufacturing methods of Examples 22-26 are basically the same as those of Example 3, except that the type of the second fluorine-containing polymer is changed. In Example 22, the second fluorine-containing polymer is polytetrafluoroethylene having a weight average molecular weight of 10,000, and the manufacturing methods are as follows:
[0211] 0.4 kg of deionized water and 0.2 g of carboxyethyl cellulose ether were added to a 1 L four-neck flask, and nitrogen gas was introduced to remove oxygen dissolved in the solution. 1.0 g of tert-amyl peroxypivalate and 0.1 g of potassium carbonate were added again, and 0.1 kg of tetrafluoroethylene was added. The mixture was mixed and stirred for 30 minutes and heated to 68°C. The polymerization reaction was carried out for 3 hours, and the polymerization solution was distilled, washed, separated, dried and pulverized to obtain polytetrafluoroethylene.
[0212] In Example 23, the second fluorine-containing polymer is a vinylidene fluoride-hexafluoropropylene copolymer having a weight average molecular weight of 10,000, and the preparation method is as follows.
[0213] 0.4 kg of deionized water and 0.2 g of carboxyethyl cellulose ether were added to a 1 L four-neck flask, and nitrogen gas was introduced to remove oxygen dissolved in the solution. 1.0 g of tert-amyl peroxypivalate and 0.1 g of potassium carbonate were added again, and 0.8 kg of vinylidene fluoride and 0.2 kg of hexafluoropropylene were added. The mixture was mixed and stirred for 30 minutes and heated to 68°C. The polymerization reaction was carried out for 4 hours, and the polymerization solution was distilled, washed, separated, dried and pulverized to obtain polyvinylidene fluoride-hexafluoropropylene.
[0214] In Example 24, the second fluorine-containing polymer is polyvinylidene fluoride having a weight average molecular weight of 10,000, and the preparation method is as follows.
[0215] Into a 1L four-neck flask, add 0.4kg of deionized water and 0.2g of carboxyethyl cellulose ether, add nitrogen gas to remove oxygen dissolved in the solution, add 1.0g of 2-ethyl peroxydicarbonate and 0.1g of sodium hydrogen carbonate again, add 0.1kg of vinylidene fluoride, mix and stir for 30 minutes, heat to 68℃, carry out polymerization reaction for 3 hours, distill, wash, separate, dry and pulverize the polymerization solution to obtain polyvinylidene fluoride with a weight average molecular weight of 10,000, i.e., a second fluorine-containing polymer.
[0216] In Example 25, the second fluorine-containing polymer is polytetrafluoroethylene having a weight average molecular weight of 10,000, and the preparation method is as follows.
[0217] In a 0.5L autoclave, 219g of deionized water and 0.1g of hydroxypropylmethylcellulose were added, and oxygen was removed by adding nitrogen gas to replace oxygen gas several times. Then, 120g of tetrafluoroethylene monomer gas was added, the reaction temperature was controlled at 50°C, and ammonium persulfate initiator was added to start the reaction. The amount of initiator added was about 15% of the total amount of monomer. The reaction pressure was controlled at 0.7MPa and the time was controlled at 1h. After the polymerization was completed, polytetrafluoroethylene was discharged from the bottom of the vessel, filtered, washed, dried and polished to obtain a powder material.
[0218] In Example 26, the second fluorine-containing polymer is a vinylidene fluoride-hexafluoropropylene copolymer having a weight average molecular weight of 10,000, and the preparation method is as follows.
[0219] In a 0.5L autoclave, 219g of deionized water and 0.1g of hydroxypropyl methylcellulose were added, and nitrogen gas was added and substituted several times to remove oxygen, after which 100g of vinylidene fluoride monomer gas and 11.9g of hexafluoropropylene were added. After the monomers were added, the reaction temperature was controlled at 85°C. After adding 0.14g of water-soluble ammonium persulfate initiator and isopropyl alcohol chain transfer agent, the reaction was started, and the amount of initiator added was about 8% of the total amount of monomer. The polymerization reaction time was 1h, and the pressure was maintained at 4.4MPa. After the reaction product was washed with water and dried, a second fluorine-containing polymer was obtained.
[0220] The types of the second fluorine-containing polymers in Examples 27-31 are the same as those in Examples 22-26, respectively, except that the weight average molecular weight of the second fluorine-containing polymer is 80,000; In Example 27, the second fluorine-containing polymer is polytetrafluoroethylene having a weight average molecular weight of 80,000, and the preparation method is as follows.
[0221] 0.4 kg of deionized water and 0.2 g of carboxyethyl cellulose ether were added to a 1 L four-neck flask, and nitrogen gas was introduced to remove oxygen dissolved in the solution. 0.9 g of tert-amyl peroxypivalate and 0.1 g of potassium carbonate were added again, and 0.1 kg of tetrafluoroethylene was added. The mixture was mixed and stirred for 30 minutes, heated to 64°C, and polymerized for 6 hours. The mixture was then distilled, washed, separated, dried, and pulverized to obtain a polymerized solution.
[0222] In Example 28, the second fluorine-containing polymer is a vinylidene fluoride-hexafluoropropylene copolymer having a weight average molecular weight of 80,000, and the preparation method is as follows.
[0223] 0.4 kg of deionized water and 0.2 g of carboxyethyl cellulose ether were added to a 1 L four-neck flask, and nitrogen gas was introduced to remove oxygen dissolved in the solution. 0.9 g of tert-amyl peroxypivalate and 0.1 g of potassium carbonate were added again, and 0.8 kg of vinylidene fluoride and 0.2 kg of hexafluoropropylene were added. The mixture was mixed and stirred for 30 minutes and heated to 64°C. The polymerization reaction was carried out for 7 hours. The polymerization solution was distilled, washed, separated, dried and pulverized to obtain polyvinylidene fluoride-hexafluoropropylene.
[0224] In Example 29, the second fluorine-containing polymer is polyvinylidene fluoride having a weight average molecular weight of 80,000, and the preparation method is as follows.
[0225] 0.4 kg of deionized water and 0.2 g of carboxyethyl cellulose ether were added to a 1 L four-neck flask, and nitrogen gas was introduced to remove the oxygen dissolved in the solution. 0.9 g of 2-ethyl peroxydicarbonate and 0.1 g of sodium hydrogen carbonate were added again, and 0.1 kg of vinylidene fluoride was added. The mixture was mixed and stirred for 30 minutes, heated to 64°C, and polymerized for 6 hours. The mixture was then distilled, washed, separated, dried, and pulverized to obtain a polymerized solution.
[0226] In Example 30, the second fluorine-containing polymer is polytetrafluoroethylene having a weight average molecular weight of 80,000, and the preparation method is as follows.
[0227] In a 0.5L autoclave, 219g of deionized water and 0.1g of hydroxypropylmethylcellulose were added, and oxygen was removed by adding nitrogen gas to replace oxygen gas several times. Then, 120g of tetrafluoroethylene monomer gas was added, the reaction temperature was controlled at 50°C, and ammonium persulfate initiator was added to start the reaction. The amount of initiator added was about 15% of the total amount of monomer. The reaction pressure was controlled at 0.7MPa and the time was controlled at 1h. After the polymerization was completed, polytetrafluoroethylene was discharged from the bottom of the vessel, filtered, washed, dried and polished to obtain a powder material.
[0228] In Example 31, the second fluorine-containing polymer is a vinylidene fluoride-hexafluoropropylene copolymer having a weight average molecular weight of 80,000, and the preparation method is as follows.
[0229] In a 0.5L autoclave, 219g of deionized water and 0.1g of hydroxypropyl methylcellulose were added, and nitrogen gas was added and substituted several times to remove oxygen, and then 100g of vinylidene fluoride monomer gas and 11.9g of hexafluoropropylene were added. After the monomers were added, the reaction temperature was controlled at 85°C. After adding 0.12g of water-soluble ammonium persulfate initiator and isopropyl alcohol chain transfer agent, the reaction was started, and the amount of initiator added was about 8% of the total amount of monomer. The polymerization reaction time was 1h, and the pressure was maintained at 4.6MPa. After the reaction product was washed with water and dried, a second fluorine-containing polymer was obtained.
[0230] In Example 32, the first fluorine-containing polymer is a vinylidene fluoride-trifluorochloroethylene copolymer with a weight average molecular weight of 3.2 million, and other details are basically the same as those in Example 3. The preparation method of the first fluorine-containing polymer is as follows:
[0231] Add 4kg of deionized water and 2g of methylcellulose ether to a 10L autoclave, evacuate and replace O2 with N2 three times, add 5g of tert-butyl peroxypivalate and 2g of sodium bicarbonate again, fill with 0.94kg of vinylidene fluoride and 0.06kg of trifluorochloroethylene, allow the system pressure to reach 7Mpa, mix and stir for 30min, heat to 45℃, react for 10h, add 20g of cyclohexane to continue the reaction, and stop the reaction when the pressure in the reactor drops to 2MPa. After centrifuging the reaction system, collect the solid phase, wash and dry to obtain vinylidene fluoride-trifluorochloroethylene polymer.
[0232] Comparative Examples 1-4 and Examples 1, 16, 19, and 32 are basically the same, with the difference being that the adhesive does not contain the second fluorine-containing polymer, but contains only the first fluorine-containing polymer.
[0233] The adhesive in Comparative Example 5 is polyvinylidene fluoride with a weight average molecular weight of 800,000, which is the 701A polyvinylidene fluoride produced by Dongyangguang Co., Ltd.
[0234] Second, battery performance test 1. Adhesive composition property test 1) Weight average molecular weight test A Waters 2695 Isocratic HPLC type gel chromatograph (differential refractive index detector 2141) was adopted. A polystyrene solution sample with a mass fraction of 3.0% was used as the standard, and a matching chromatographic column (oil-based: Styragel HT5DMF7.8*300mm+Styragel HT4) was selected. A 3.0% adhesive glue solution was prepared with purified N-methylpyrrolidone (NMP) solvent, and the prepared solution was left to stand for one day in preparation for use. During the test, tetrahydrofuran was first aspirated with a syringe, washed, and repeated several times. Then 5 ml of the experimental solution was aspirated, the air in the syringe was eliminated, and the needle tip was wiped and dried. Finally, the sample solution was slowly injected into the injection port. When the display value became stable, the data was acquired and the weight average molecular weight was read.
[0235] 2) Polydispersity coefficient test A Waters 2695 Isocratic HPLC type gel chromatograph (differential refractive index detector 2141) was adopted. A polystyrene solution sample with a mass fraction of 3.0% was used as the standard, and a matching chromatographic column (oil-based: Styragel HT5DMF7.8*300mm+Styragel HT4) was selected. A 3.0% adhesive glue solution was prepared with purified N-methylpyrrolidone (NMP) solvent, and the prepared solution was left to stand for one day in preparation for use. During the test, tetrahydrofuran was first sucked into the syringe, washed, and repeated several times. Then 5 ml of the experimental solution was sucked, the air in the syringe was eliminated, and the needle tip was wiped and dried. Finally, the sample solution was slowly injected into the injection port. When the displayed value became stable, the data was acquired. The weight average molecular weight a and the number average molecular weight b were read, respectively. The polydispersity coefficient = a / b.
[0236] 3) Dv50 test Referring to GB / T 19077-2016 Particle size distribution laser diffraction method, 0.1g-0.13g of the first fluorine-containing polymer powder was weighed in a 50ml beaker, and 5g of anhydrous ethanol was weighed and added to the beaker containing the first fluorine-containing polymer powder, and a stirrer with a length of about 2.5mm was put in and sealed with plastic wrap. The sample was put into an ultrasonic machine and ultrasonicated for 5min, then transferred to a magnetic mixer and stirred at 500r / min for more than 20min, and two samples were extracted and tested for each lot of products, and the average value was taken. A laser particle size analyzer was used for measurement, for example, a Mastersizer 2000E type laser particle size analyzer manufactured by Malvern Instruments Ltd. in the UK was used to carry out the test.
[0237] 4) Crystallinity test 0.5 g of the first fluorine-containing polymer was placed in an aluminum crucible, flattened, and the crucible was covered with a lid. In a nitrogen gas atmosphere, with a purge gas of 50 ml / min and a protective gas of 70 ml / min, the heating rate was 10°C / min, and the test temperature range was -100°C to 400°C. The test was performed using a US TA Instruments Model Discovery 250 differential scanning calorimeter (DSC) to remove thermal history.
[0238] In this test, obtain the temperature change curve of DSC / (Mw / mg) of the first fluorine-containing polymer, integrate, and the peak area is the melting enthalpy ΔH (J / g) of the first fluorine-containing polymer, and the adhesive crystallinity=ΔH / (ΔHm100%)*100%, where ΔHm100% is the standard melting enthalpy (crystallization heat of fusion) of the fluorine-containing polymer, and ΔHm100%=104.7 J / g.
[0239] 5) Viscosity test of glue solution Weigh out 14g of the first fluorine-containing polymer and 336g of N-methylpyrrolidone (NMP) in a 500ml beaker, and prepare a glue solution with a mass fraction of 4%. Use a Lichen high-speed grinder to mix and disperse the solution. Rotation speed is 800r / min, and after 120min of mixing, ultrasonic vibration is used for 30min to remove bubbles. At room temperature, use Lichen Technology NDJ-5S rotational viscometer to test the solution. Select a No. 3 rotor and insert it into the glue solution, ensure that the rotor liquid level mark and the glue solution liquid level are on the same surface, and test the viscosity at a rotor rotation speed of 12r / min, and read the viscosity data after 6min.
[0240] 6) Terminal group test The end group structure of the polymer was studied by the method of nuclear magnetic resonance. The nuclear magnetic instrument was a Bruker AV400 instrument. 19 F-NMR and 1 The polymer end group structure was analyzed by H-NMR. Dimethylsulfoxide was used as the solvent, CFCl3 was used as the fluorine spectrum standard, and TMS was used as the hydrogen spectrum standard. 19 The F-NMR acquisition time was 0.33 s, the number of scans was 64, the pulse delay was 2 s, and the pulse width was 5 μs. 1 The acquisition time for H-NMR analysis was 2.2 s, the number of scans was 16, the pulse delay was 2 s, and the pulse width was 33 μs.
[0241] 2. Slurry performance test 1) Slurry fluidity test An appropriate amount of the positive electrode slurry was taken with a chemical spoon, and the slurry was observed to see if it naturally flowed smoothly. If it naturally flowed smoothly, it was judged as OK, but if the fluidity was poor and the slurry became jelly-like and formed lumps, indicating the appearance of gel, it was judged as NG.
[0242] 2) Slurry filtration performance test A 500 ml beaker was placed on the lower end of the 200 mesh filter bracket, 500 ml of the slurry was taken and placed on the filter to filter, and the time when the slurry volume in the beaker reached 300 ml was recorded. This time was used to judge the filtration performance of the slurry. If the filtration time was less than 120 s, it indicated that the filtration performance of the slurry was OK, and if the slurry could not pass through the filter, it indicated that the filtration performance of the slurry was poor and was judged as "NG".
[0243] 3. Electrode plate performance test 1) Adhesion test According to the national standard GB-T2790-1995 "Testing method for 180° peel strength of adhesives", the adhesive strength testing process of the examples and comparative examples of this application is as follows:
[0244] A blade was used to cut out a sample with a width of 30 mm and a length of 100-160 mm, and a special double-sided tape was attached to a steel plate, making the tape width 20 mm and the length 90-150 mm. The positive electrode film layer surface of the electrode plate sample cut in the previous step was attached to the double-sided tape, and then rolled three times in the same direction with a 2 kg press roller.
[0245] A paper tape having the same width as the electrode plate and a length of 250 mm was fixed to the electrode plate current collector and was also fixed with masking tape.
[0246] The power supply of the Sansi tensioning machine (sensitivity is 1N) was turned on, the indicator lamp was lit, the stopper block was adjusted to the appropriate position, and the end of the steel plate where the electrode plate was not attached was fixed with the lower jig. The paper tape was folded up and fixed with the upper jig, and the position of the upper jig was adjusted using the "up" and "down" buttons on the manual controller attached to the tensioning machine. Then the test was performed and the numerical value was read. The force when the electrode plate was balanced under the force was divided by the width of the tape to characterize the adhesive strength of the electrode plate per unit length, which was the adhesive strength between the positive electrode film layer and the current collector.
[0247] 2) Measurement of positive electrode film layer resistance: The dried positive electrode slurry (film layer) was cut from the left, center, and right of the positive plate, and cut into small rings with a diameter of 3 mm. Turn on the Yuan Neng Technology plate resistor, place it on the appropriate position of the plate resistor's "probe", click the "Start" button, and read the display value when it becomes stable. Each small ring is tested in two positions, and finally calculate the average value of the six measurements, which is the film layer resistance of this plate.
[0248] 3) Plate brittleness test The positive electrode plate in the embodiment was cut into a test sample of 20 x 100 mm in size and prepared for use. The electrode plate was bent and folded in half, fixed, and pressed once with a 2 kg roller, and the presence or absence of light transmission and metal breaks at the folded part of the electrode plate was checked. If there was no light transmission or metal breaks, the electrode plate was folded in half again, fixed, pressed once with a 2 kg roller, and the presence or absence of light transmission and metal breaks at the folded part of the electrode plate was checked. The above steps were repeated until there was light transmission and metal breaks at the folded part of the electrode plate, and the number of light transmissions of the folded positive electrode plate was recorded. Three sets were measured in parallel, and the average value was calculated.
[0249] 4. Battery performance test 1) Battery capacity retention test The battery capacity retention test process is as follows: At 25℃, the button battery is charged to 3.65V at 1 / 3C constant current, then charged to 0.05C at 3.65V constant voltage, left for 5min, and discharged to 2.5V at 1 / 3C, the resulting capacity is the initial capacity C0. The above steps are repeated for the same battery, and the discharge capacity Cn of the battery after the nth cycle is recorded at the same time. The battery capacity retention after each cycle is Pn=Cn / C0*100%, and the values of these 500 points P1, P2...P500 are taken as the ordinate and the corresponding cycle number is taken as the abscissa to obtain a curve of battery capacity retention vs cycle number.
[0250] In this test process, the first cycle corresponded to n = 1, the second cycle corresponded to n = 2, ... the 500th cycle corresponded to n = 500. The battery capacity retention data in Table 1-6 corresponding to Examples 1 to 41 or Comparative Examples 1 to 3 are data measured after 500 cycles under the above test conditions, i.e., the P500 value.
[0251] 3. Analysis of the Test Results of Each Example and Comparative Example According to the above-mentioned method, the batteries of the examples and comparative examples were manufactured, and the performance parameters were measured. The results are shown in the following Tables 1 to 6.
[0252] [Table 1] [Table 2] [Table 3] [Table 4] [Table 5] [Table 6]
[0253] [Table 7] [Table 8]
[0254] As can be seen from the comparison between Examples 1-32 and Comparative Example 5, the adhesive composition includes a first fluorine-containing polymer and a second fluorine-containing polymer, the weight average molecular weight of the first fluorine-containing polymer is 1.5 million to 5 million, and the weight average molecular weight of the second fluorine-containing polymer does not exceed 600,000. Compared with the polyvinylidene fluoride adhesive having a weight average molecular weight of 800,000 used in the conventional technology, the adhesive composition according to the present application effectively improves the adhesive performance of the electrode plate and reduces the amount of adhesive used.
[0255] As can be seen from Examples 1-32, the first fluorine-containing polymer includes structural units derived from vinylidene fluoride and may be a homopolymer or a copolymer, and the second fluorine-containing polymer includes at least one of polytetrafluoroethylene, polyvinylidene fluoride, and poly(vinylidene fluoride-hexafluoropropylene) copolymer.
[0256] As can be seen from the comparison between Examples 1-9 and Comparative Example 1, compared with the case where the large molecule polyvinylidene fluoride adhesive is used alone, the adhesive composition having a mass content of the second fluorine-containing polymer of 0.1% to 10% based on the total mass of the adhesive composition can maintain high adhesive performance while optimizing the processing performance of the adhesive, improving the uniformity of the electrode plate, and further improving the cycle performance of the battery. With an increase in the content of the second fluorine-containing polymer used in the adhesive composition, the adhesive strength of the adhesive composition gradually decreases, the crystallinity first decreases and then increases, and the flexibility of the electrode plate first increases and then decreases.
[0257] As can be seen from the comparison between Examples 10-21 and Comparative Example 1, when the weight average molecular weight of the second fluorine-containing polymer is 5,000-600,000, the addition of the second fluorine-containing polymer can better optimize the overall performance of the battery, including adhesion performance, processability, flexibility and cycle performance.
[0258] As can be seen from Examples 22-32, when the end group of the second fluorine-containing polymer contains a hydroxyl group or an ester group, the addition of the second fluorine-containing polymer can improve the slurry processability and, at the same time, can further improve the retention of the electrode plate adhesion performance without significantly decreasing the electrode plate adhesion performance.
[0259] It should be noted that the present application is not limited to the above-mentioned embodiment. The above-mentioned embodiment is merely an example, and any embodiment having substantially the same configuration as the technical idea and achieving the same effect within the scope of the technical solution of the present application is included in the technical scope of the present application. In addition, various modifications that a person skilled in the art can make to the embodiment and other methods configured by combining some of the components in the embodiment are also included in the scope of the present application, within the scope of the purpose of the present application. [Explanation of symbols]
[0260] 1 battery pack, 2 upper housing, 3 lower housing, 4 battery module, 5 secondary battery, 51 case, 52 electrode assembly, 53 cover plate.
Claims
1. An adhesive composition comprising a first fluorine-containing polymer and a second fluorine-containing polymer, the first fluorine-containing polymer having a weight average molecular weight of 1.5 million to 5 million, and the second fluorine-containing polymer having a weight average molecular weight not exceeding 600,000.
2. 2. The adhesive composition according to claim 1, wherein the mass content of the second fluorine-containing polymer is 0.1% to 10%, based on the total mass of the adhesive composition.
3. 3. The adhesive composition according to claim 1 or 2, characterized in that the adhesive composition has a crystallinity of less than 45%, optionally 15%-45%.
4. The adhesive composition according to any one of claims 1 to 3, wherein the first fluorine-containing polymer contains a structural unit derived from vinylidene fluoride.
5. The first fluorine-containing polymer further comprises a structural unit shown in formula I, 【Chemistry 1】 Here, R 1 The adhesive composition according to any one of claims 1 to 4, characterized in that contains one or more of hydrogen, fluorine, chlorine, and a trifluoromethyl group.
6. The adhesive composition according to any one of claims 1 to 5, characterized in that the polydispersity coefficient of the first fluorine-containing polymer is from 1.5 to 2.5, and optionally from 2 to 2.
3.
7. The adhesive composition according to any one of claims 1 to 6, wherein the crystallinity of the first fluorine-containing polymer is 34% to 48%, optionally 40%-48%.
8. The adhesive composition according to any one of claims 1 to 7, characterized in that the viscosity of a glue solution containing the first fluorine-containing polymer at a mass content of 4% produced by dissolving the first fluorine-containing polymer in N-methylpyrrolidone is 2400 mPa·s to 5000 mPa·s, and optionally 3500 to 5000 mPa·s.
9. The adhesive composition according to any one of claims 1 to 8, wherein the first fluorine-containing polymer comprises one or more of polyvinylidene fluoride, vinylidene fluoride-trifluorochloroethylene copolymer, vinylidene fluoride-hexafluoropropylene copolymer, vinylidene fluoride-trifluorochloroethylene-hexafluoropropylene copolymer, vinylidene fluoride-tetrafluoroethylene-hexafluoropropylene copolymer, and vinylidene fluoride-trifluorochloroethylene-tetrafluoroethylene-hexafluoropropylene copolymer.
10. The second fluorine-containing polymer comprises a structural unit shown in Formula II, 【Chemistry 2】 Here, R 2 , R 3 each independently represents a C group containing hydrogen, a halogen, and at least one fluorine atom; 1-3 The adhesive composition according to any one of claims 1 to 9, further comprising at least one alkyl group.
11. R 2 , R 3 The adhesive composition according to any one of claims 1 to 10, wherein each independently contains at least one of hydrogen, fluorine, chlorine, and a trifluoromethyl group.
12. The adhesive composition according to any one of claims 1 to 11, wherein an end group of the second fluorine-containing polymer contains a hydroxyl group or an ester group.
13. The adhesive composition according to any one of claims 1 to 12, wherein the second fluorine-containing polymer has a weight average molecular weight of 5,000 to 600,000.
14. The adhesive composition according to any one of claims 1 to 13, wherein the second fluorine-containing polymer comprises one or more of polytetrafluoroethylene, polyvinylidene fluoride, poly(vinylidene fluoride-hexafluoropropylene) copolymer, poly(vinylidene fluoride-tetrafluoroethylene) copolymer, poly(vinylidene fluoride-chlorofluoroethylene) copolymer, and poly(vinylidene fluoride-tetrafluoroethylene-hexafluoropropylene) copolymer.
15. A method for producing an adhesive composition, comprising the steps of: Preparation of a first fluorine-containing polymer: carrying out a first polymerization reaction on a raw material containing a vinylidene fluoride monomer under polymerization conditions to prepare a first fluorine-containing polymer, and the weight average molecular weight of the first fluorine-containing polymer is 1.5 million to 5 million; Preparation of a second fluorine-containing polymer: carrying out a second polymerization reaction on a raw material containing vinylidene fluoride monomer under polymerization conditions to prepare a second fluorine-containing polymer, and the weight average molecular weight of the second fluorine-containing polymer is not more than 600,000; Blending: A method for producing an adhesive composition, comprising blending a first fluorine-containing polymer with a second fluorine-containing polymer to produce an adhesive composition.
16. The first method for producing a fluorine-containing polymer includes the steps of: carrying out a first polymerization reaction for 6 hours to 12 hours in a non-reactive gas atmosphere at a reaction pressure of 6 MPa to 8 MPa and a reaction temperature of 45° C. to 60° C. with respect to a raw material containing vinylidene fluoride monomer; The method according to claim 15, further comprising: adding a chain transfer agent, lowering the pressure in the reaction system to 2 MPa to 2.5 MPa, stopping the reaction, and performing solid-liquid separation to leave a solid phase to obtain a first fluorine-containing polymer.
17. The second method for producing a fluorine-containing polymer includes the steps of: A second polymerization reaction is carried out for 0.5 to 8 hours with at least one monomer represented by formula III in a non-reactive gas atmosphere at 0.1-5 MPa and a reaction temperature of 60°C to 90°C, and the reaction is terminated and separated into a solid and liquid to leave a solid phase, thereby obtaining a second fluorine-containing polymer; 【Chemistry 3】 Here, R 4 , R 5 each independently represents a C group containing hydrogen, a halogen, and at least one fluorine atom; 1-3 The method according to claim 15 or 16, characterized in that it comprises at least one alkyl group.
18. The second polymerization reaction is adding a solvent and a dispersant to a vessel and filling said vessel with a non-reactive gas; 18. The method of any one of claims 15 to 17, further comprising the steps of adding the monomer of formula III, raising the temperature to 60°C to 90°C, and then adding a second initiator and a chain transfer agent to carry out a second polymerization reaction.
19. 20. The process of claim 18, wherein the second initiator comprises an inorganic peroxide and may be selected from potassium persulfate or ammonium persulfate.
20. 20. The method according to claim 18 or 19, characterized in that the mass content of the initiator is 3%-12%, based on the total mass of the monomers shown in formula III.
21. 21. The process of any one of claims 16 to 20, wherein the chain transfer agent comprises one or more of cyclohexane, isopropyl alcohol, methanol, and acetone.
22. 22. A positive electrode plate comprising: a positive electrode current collector; and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, the positive electrode film layer comprising a positive electrode active material, a conductive agent, and the adhesive composition according to any one of claims 1 to 14 or an adhesive composition produced by the production method according to any one of claims 15 to 21.
23. The positive electrode plate of claim 22 , wherein the mass fraction of the adhesive composition does not exceed 1.2% based on the total mass of the positive electrode membrane layer.
24. 24. The positive electrode plate according to claim 22 or 23, characterized in that the positive electrode active material is a transition metal oxide containing lithium, and optionally at least one of lithium iron phosphate or lithium nickel cobalt manganese oxide, or a doping modification thereof, or a conductive carbon-coated modification thereof, a conductive metal-coated modification thereof, or a conductive polymer-coated modification thereof.
25. 25. A secondary battery comprising an electrode assembly and an electrolyte, the electrode assembly comprising a separator, a negative electrode plate, and the positive electrode plate according to claim 22.
26. A power consuming device comprising the secondary battery of claim 25.
Citation Information
Patent Citations
Adhesive composition
CN109929482A
Binder solution, cathode mixture and anode mixture
JP2013229337A
Separation film for secondary battery, and lithium secondary battery including the same
JP2017208338A
Electrode for non-aqueous electrolyte secondary battery
JP2020113442A
Self-checkout apparatus of controlling conveying of goods
KR102044125B1
